Behavior of electrical charge storage/release in polyaniline electrodes of symmetric supercapacitor. (10th August 2017) - Gu, Dawei; Ding, Chao; Qin, Yilong; Jiang, Hongying; Wang, Lei; Shen, Linjiang
Graphical abstract: Highlights: The capacitance of Pani in the different potential range was dominated by the different mechanisms. The EDLC or PSC mechanism dominating the electrode depended on potential of Pani electrode that was either higher or lower than the redox potential of Pani. The operation mechanisms of the positive and negative electrodes for a Pani symmetric supercapacitor are asymmetric. Abstract: This account investigated the behavior of the electrical charge storage/release in polyaniline (Pani) electrodes of a symmetric supercapacitor with 0.5 M H2 SO4 electrolyte. Two Pani films with different morphologies were synthesized under various reaction pressures. The structural and morphological characterizations of Pani films were carried out by Fourier Transform infrared spectroscopy (FTIR) and Field emission scanning electron microscopy (FESEM). The electrochemical behavior of Pani films was characterized by several methods, including cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) cycling and electrochemical impedance spectroscopy (EIS). The performance of the electrodes assembled in a symmetric supercapacitor configuration was also characterized by GCD in different voltage windows. The contributions from the electric double-layer capacitance (EDLC) and the pseudo-capacitance (PSC) of Pani electrodes at different potential windows were evaluated and compared. The results suggested that the specific capacitance induced from EDLC and PSC for Pani films with porous nano-network morphology were obviously higher than those generated by the granular Pani films. This was attributed to the porous nano-network structure, which had a significant role in increasing the specific surface area. For symmetric Pani supercapacitors, the induced capacitance at the negative electrode was found dominated by PSC while accumulation/release of the electric charge at the positive electrode mainly followed an EDLC mechanism. The redox potential of Pani played a cut-off point between the potential range dominated by EDLC and PSC mechanisms. A working model was proposed to describe the electrical charge storage/release processes at different electrodes assembled in a symmetric capacitor configuration.